A Simple Procedure to Fabricate Paper Biosensor and Its Applicability—NADH/NAD+ Redox System - Coutinho, Isabel Cristina Ribau Fernandes (2019)
A simple device which incorporates three electrodes (working electrode, counter electrode and reference electrode) was constructed to be used currently in laboratories without elevated cost. It does not need more than 2 μL of electrolyte, sample or working solution, his support material is paper, and the working electrode which is based on carbon ink can incorporate enzymes and cofactors. To test this concept we started this investigation using the NADH/NAD+ redox couple which is an omnipresent coenzyme in living systems but is also a challenge to electrochemistry. The paper sensor fabrication was simple, rapid and cheaper. NADH was incorporated in the carbon ink by mixing both and, this mixture was used to print the working electrode. The direct electrochemical system NADH/NAD+ signal obtained, using this device, appeared at low potentials. A quasi-reversible diffusional redox process was achieved and regeneration of the NADH after oxidation was reached. This small paper device was not only used to study the redox process of NAD+/NADH, but also its behavior in the presence of electroactive (ascorbic acid) and non-eletroactive species (glucose).